The reasons why athletes squat deep in Japan Volleyball Women`s National Team. - Kotani, Y.; Hori, N. (Journal of Australian Strength and Conditioning, 2017)
The squat is one of the most common exercises for strengthening lower extremities. While this exercise can be performed with shallower or deeper range of motion, our athletes train with deep squats (front of thigh below parallel to the floor, or 120-140° knee flexion) in the Japan Volleyball Women`s National Team. It is because literature has suggested that the deep squat improved vertical jump performance more than the shallow squat. This article synthesizes available literature and provides readers our rationale of why athletes should train with deep squats.